Sense Of Place And Haptic Heritage Of Penang Chinese Peranakan Domestic Spaces: From Kitchen To Table - Prihatmanti, Rani (2024)
Food is one of the quintessential elements in the everyday life in the Chinese Peranakan household. To them, food is not only for daily consumption, but it is also for celebration and religious offerings. The transformation process of ingredients by manipulating the kitchen tools are performed according on the haptic knowledge and experience were inherited from one generation to another. Hence, there is a strong connection between the memory and the senses behind the production of Nyonya foods. This particularly the haptic sensuous organs which are used to perceive the space and place through movement and locomotion. Unfortunately, the young generations are now modernised and little of them are practicing these cultural beliefs. Because of the rapid modernisation and westernisation, safeguarding the cultural elements of Chinese Peranakan culture is imperative. In related to that, this research looks on the haptic heritage behind the production of Nyonya foods in Penang Chinese Peranakan household. Haptic experience which implanted over the time will develop the ‘Sense of Place’ to the Chinese Peranakan descendants towards their domestic spaces. Thus, the main objective of this research is to investigate the correlation between haptic heritage and ‘Sense of Place’ in the domestic spaces of Penang Chinese Peranakan household. This study adopts Lefebvre’s Space Triad to examine the domestic spaces and to experienced it on the lived experience of the Penang Chinese Peranakan descendants. This research is qualitative with inductive approach that delves into ethnography, phenomenology, and case study. Seven Penang Chinese Peranakan descendants aged between 60 to 90 years were also interviewed.